Exploring the Potential of Traditional Medicinal Plants for Central Nervous System Related Activity - Santra, Sougata; Hussain, Adib; Nayak, Arabinda (Pharmacognosy Reviews)
People have used native healing plants in different old-school medicine practices worldwide for hundreds of years to fix all sorts of health problems, including ones that mess with the brain and nerves. As science gets better, folks are getting excited again about checking out what these plants can do for brain and nerve issues like feeling worried or down, seizures, trouble sleeping mixed-up thinking, and brain diseases that get worse over time like forgetting everything, shaking a lot or not being able to control your movements. The brain and nerves are super complicated and coming up with treatments that can change how they work without causing too many problems is one of the biggest headaches in medicine today. That's where these native healing plants come in handy. They're full of natural stuff that might work as safer options or add-ons to regular treatments for brain and nerve problems. A bunch of these plants have active ingredients like alkaloids, flavonoids, terpenoids, glycosides, saponins, polyphenols, and tannins. These ingredients do their thing in different ways, like changing how brain chemicals work (like serotonin, dopamine, GABA glutamate) helping the body fight off damage, cutting down on brain swelling, and helping new brain cells grow. For example, alkaloids like nicotine and caffeine have been known to wake up the brain for a long time, while flavonoids like quercetin and rutin are known to protect brain cells and fight swelling. Certain terpenoids such as those in Cannabis sativa, have a big impact on the central nervous system. Their effects range from pain relief to anxiety reduction. Several native medicinal plants have caught the eye of researchers because of how they affect the central nervous system.
Keywords: Herbal medicine; Neuroprotection; Healing Agents; Active Ingredients; Treatments